Chilled ceiling air-conditioning for tropical climates : experimental investigation - Teoh, Benjamin Yew Heng (2014)
This report describes the design and improvement of the condition and method of testing of a single chilled water panel in a test compartment. The purpose is to provide a test set up that can determine the cooling capacity of any given panel design so that it could be rated at an acceptable temperature difference between the mean chilled water temperature and the reference room temperature. Test parameters such as the supply flow rate of chilled water, inlet and outlet temperatures of chilled water at the panel, air and globe temperatures are recorded at steady state condition and their results are analysed to help with the improvement of the test set up much like an iterative process. Recommendations to the test setup after using a generic single chilled water panel for testing include using lower flow rate for more measurable inlet and outlet temperature difference, increasing insulation thickness and air tightness of the test compartment and using of smaller heat loads for the energy balance to prevent high reference room temperatures.